1991
DOI: 10.1073/pnas.88.18.7993
|View full text |Cite
|
Sign up to set email alerts
|

Identification of monoclonal antibody epitopes and critical residues for rhinovirus binding in domain 1 of intercellular adhesion molecule 1.

Abstract: Intercellular adhesion molecule 1 (ICAM-1) is the cellular receptor for the major group of human rhinoviruses (HRVs) and the adhesion ligand of lymphocyte function-associated antigen 1. Analysis of a series of chimeric exchanges between human and murine ICAM-1 shows that two distinct epitopes recognized by monoclonal antibodies that block rhinovirus attachment and cell adhesion map to the N-terminal first domain of ICAM-1. Furthermore the specificity for HRV binding is entirely contained within the first 88 am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
69
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 25 publications
3
69
0
Order By: Relevance
“…Of special interest is Pro70 of ICAM-1 that is stacked on top of Pro3178 in HRV14 or on top of the equivalent Pro3180 in HRV16. When Pro70 is mutated to almost any other amino acid, the binding between receptor and virus is eliminated (32,41). Another hydrophobic residue, Phe3086 in HRV14 (Tyr3086 in HRV3), is close to the Pro70-Pro3178 interaction, which may further enhance the local hydrophobic environment.…”
Section: Resultsmentioning
confidence: 99%
“…Of special interest is Pro70 of ICAM-1 that is stacked on top of Pro3178 in HRV14 or on top of the equivalent Pro3180 in HRV16. When Pro70 is mutated to almost any other amino acid, the binding between receptor and virus is eliminated (32,41). Another hydrophobic residue, Phe3086 in HRV14 (Tyr3086 in HRV3), is close to the Pro70-Pro3178 interaction, which may further enhance the local hydrophobic environment.…”
Section: Resultsmentioning
confidence: 99%
“…The media were removed and the cells fixed for 10 minutes at 23°C with 3.7% formalin in PBS. The cells were washed and then incubated with a 1:1,OOO dilution of the first antibody (anti-ICAM-1 C78.5 [14]; kindly supplied by Dr. J. Greve, Molecular Therapeutics Inc., West Haven, CT) or nonimmune control IgG in PBS-0.1% BSA for 2 hours at 23°C. The cells were washed in PBS-BSA, then blocked for 1 hour in PBS-3% BSA.…”
Section: Methodsmentioning
confidence: 99%
“…ceptor function, although the efficiency of binding and infection was increased by the addition of some, but not all, heterologous immunoglobulin-like domains (18)(19)(20)41).…”
Section: Discussionmentioning
confidence: 99%
“…However, studies with PV, HRV, and hepatitis A virus (HAV) have shown that deletion of the membrane-proximal extracellular domains decreases virus binding to the receptor, as well as infection of the cells (13,(15)(16)(17). Replacement of these proximal domains with homologous domains from other species restored normal receptor function (18,19), but replacement with heterologous protein domains did not (16,20). Thus, domains that are located membrane proximal to the virus-binding D1 domain are important to maintain virus receptor properties, but the mechanisms that are involved are not well understood.…”
mentioning
confidence: 99%
See 1 more Smart Citation